Efficacy of Biodegradable Polydioxanone and Polylactic Acid Braided Biodegradable Biliary Stents for the Management of Benign Biliary Strictures - Zhang, Weixing; Kanwal, Fariha; ur Rehman, Muhammad Fayyaz; Wan, Xinjian (Turkish Journal of Gastroenterology, 2021)
Background: Benign biliary strictures (BBS) are widely treated by endoscopic procedures involving temporary stent placement. Occasionally, stents are required to be removed, making the treatment process very painful as well as expensive. Until now, no effective biodegradable biliary stents are available for clinical applications. This study aims to investigate the safety and efficacy of biodegradable polydioxanone (PDO) and polylactic acid (PLA) braided biodegradable biliary stents (BDBS) both in vitro and in vivo. Methods: Three different diameter monofilaments of PDO (0.30, 0.35, and 0.40 mm) and PLA (0.10, 0.15, and 0.20 mm) were braided to biliary stents and their mechanical properties were studied. The stents were placed in an ex vivo bile duct model perfused with porcine bile, taken out, and observed every week until these were completely degraded. After the bile duct stenosis model was established successfully in piglet, stents with appropriate mechanical properties were further examined under endoscopy; haematology, patency time of stents, and pathological changes were observed for eight months. Results: A total of 10 pigs were included (two groups; 5 PDO, 5 PLA) in the study. The patency time of the PLA group was significantly longer than that of the PDO stent group (25.7 ± 5.6w vs 11.3 ± 3.4w, respectively) in pigs. Conclusion: Our results prospect biodegradable PLA and PDO braided biliary stents could be a better choice to treat benign biliary strictures while degrading at different rates.